Nomograms for predicting the prognosis in multiple primary esophageal squamous cell carcinoma - Kexi Wang; Jian Zhong; Danting Su; Changsen Leng; Jianhua Fu; Qianwen Liu (Annals of Medicine)
Background Due to its rarity, it is challenging to predict the survival of patients with synchronous multiple primary esophageal squamous carcinomas (SMPESCs). We aimed to construct nomograms to predict survival outcomes and help to make therapeutic strategy for patients with SMPESCs.Materials and Methods The clinical and survival data of 135 patients with SMPESCs were analyzed retrospectively. Univariate and multivariate Cox analyses were used to identify independent prognostic factors. Nomograms were constructed to predict 1-year, 3-year and 5-year disease-free survival (DFS) and overall survival (OS). In addition, we further evaluated the effect of postoperative adjuvant therapy on SMPESCs patients with lymph node metastasis.Results In univariate and multivariate analyses of DFS and OS, age, site of the main lesion, lymph node metastasis, total number of lymph nodes dissected, lactate dehydrogenase level and lymphocyte-to-monocyte ratio were identified as independent prognostic factors. These characteristics were further included to establish nomograms. For the internal validation of the nomogram predictions of survival outcomes, the concordance indices were 0.752 and 0.756, respectively. Decision curve analysis also proved the efficacy of the nomograms. Furthermore, adjuvant therapy had a statistically significant benefit for OS but not DFS in patients with lymph node metastasis.Conclusions These nomograms could effectively predict the 1-year, 3-year and 5-year survival outcomes of patients with SMPESCs. Furthermore, adjuvant therapy has the potential to improve OS in patients with lymph node metastasis.